PENGARUH PELATIHAN DAN KOMPETENSI TERHADAP KINERJA PEGAWAI MELALUI EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL MEDIASI PADA SEKRETARIAT DAERAH KABUPATEN JEMBRANA - ARIE SISWOYO (GANEC SWARA, 2024)
The objective of this study is to examine the impact of training and competency on employee performance, with Employee Engagement serving as a mediating factor at the Jembrana Regency Regional Secretariat. The study population encompasses all employees of the Jembrana Regency Regional Secretariat, with 103 respondents selected using the probability sampling method. Path analysis is used in the study to evaluate the research hypothesis. The results show that: 1) Employee Engagement at the Jembrana Regency Regional Secretariat is positively and significantly influenced by training; 2) Employee Engagement at the Jembrana Regency Regional Secretariat is positively and significantly influenced by competency; 3) Employee performance at the Jembrana Regency Regional Secretariat is positively and significantly influenced by training; 4) Employee Engagement at the Jembrana Regency Regional Secretariat is positively and significantly influenced by competency; 5) Employee Engagement at the Jembrana Regency Regional Secretariat positively and significantly affects employee performance at the Jembrana Regency Regional Secretariat is positively and significantly influenced by training; 6) Employee Engagement can act as a mediating variable in the relationship between training and the performance of Jembrana Regency Regional Secretariat employ. This study recommends that the leadership of the Jembrana Regency Regional Secretariat should aim to enhance training, competency, and Employee Engagement to boost employee performance